The drainage basin as analytical framework in environmental history (Revista de História Regional, 2007)
The paper defends the use of hydrographic basins as analytic spatial outlines in environmental history. Using as empirical background the timber exploitation of colonial era, the author searches to legitimate its validity as a geographical entity integrator of a natural process the draining of superficial waters , and a mode of extraction socially and historically determined. Thus, emerges the concept of timbering basins. It is shown that the greater basin in Rio de Janeiros captaincy both in territorial range terms, and production level was the one around the Macacu river, that drains all the northeastern portion of Guanabara hydrographic region.